2020
DOI: 10.1111/anu.13167
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dietary encapsulated organic salts (Na‐acetate, Na‐butyrate, Na‐lactate and Na‐propionate) on growth performance, haemolymph, antioxidant and digestive enzyme activities and gut microbiota of juvenile narrow clawed crayfish, Astacus leptodactylus leptodactylus Eschscholtz, 1823

Abstract: A 63‐day experiment was done to study the effects of four levels (5, 10, 20 and 50 g/kg) of encapsulated organic salts (Na‐acetate, Na‐butyrate, Na‐lactate and Na‐propionate) on the growth indices and haemato‐immunological responses of crayfish Astacus leptodactylus leptodactylus (4.38 ± 0.08 g). Crayfish were distributed at 51 1,000‐L tanks (17 treatments at triplicate). The highest values of final weight (27.86 g), specific growth rate (2.94% body weight per day) and survival rate (96%) were observed in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 57 publications
1
17
0
Order By: Relevance
“…Several studies reported improved growth performance, nutrient utilization and immune response in crustaceans fed a microencapsulated blend of organic acid or acid salts. Safari et al [61] reported the efficacy of an encapsulated blend of Na-butyrate, Na-lactate and Na-propionate on growth performance and survival of crawfish at 20 g/kg. The OS blend used in the present study contains Ca-propionate, Ca-formate and Na-acetate, and showed higher feed intake compared to those fed the OA diets.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies reported improved growth performance, nutrient utilization and immune response in crustaceans fed a microencapsulated blend of organic acid or acid salts. Safari et al [61] reported the efficacy of an encapsulated blend of Na-butyrate, Na-lactate and Na-propionate on growth performance and survival of crawfish at 20 g/kg. The OS blend used in the present study contains Ca-propionate, Ca-formate and Na-acetate, and showed higher feed intake compared to those fed the OA diets.…”
Section: Discussionmentioning
confidence: 99%
“…The type and dose of SCFA salts have important effects on the growth performance of aquatic animals. Supplements of SA (3.07%), SP (3.18%) and SB (3.35%) in the diet can improve SGR, survival rate and FE of Astacus leptodatylus (Safari et al, 2020). A significant improvement in growth performance was achieved with an inclusion level of butyric acid (0.5%) in Lates calcarifer (Alamifar et al, 2019) and microencapsulated SB (0.03%) in C .…”
Section: Discussionmentioning
confidence: 99%
“…To evaluate the effects of SA, SP and SB on specific growth rate, survival rate, feed efficiency and relative percent survival, the individuals from each group were weighed and calculations were made according to a previous report (Safari et al, 2020): Specific growth rate (SGR, %/day) = 100 × (In (final body weight) – In (initial body weight))/feeding days; Survival rate (SR, %) = 100 × final survival individuals/initial individuals; Feed efficiency (FE) = (final body weight − initial body weight)/feed intakes; Relative percent survival (RPS) = (mortality rate in control group − mortality rate in immunized group)/ mortality rate in control group …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations